Foreign in two homelands : racism, return migration, and Turkish-German history - Kahn, Michelle Lynn (Publications of the German Historical Institute., 2024)
What happens when migrants are rejected by the host society that first invited them? How do they return to a homeland that considers them outsiders? Foreign in Two Homelands explores the transnational history of Turkish migrants, Germany's largest ethnic minority, who arrived as 'guest-workers' (Gastarbeiter) between 1961 and 1973. By the 1980s, amid rising racism, neo-Nazis and ordinary Germans blamed Turks for unemployment, criticized their Muslim faith, and argued they could never integrate. In 1983, policymakers enacted a controversial law: paying Turks to leave. Thus commenced one of modern Europe's largest and fastest waves of remigration: within one year, 15% of the migrants-250,000 men, women, and children-returned to Turkey. Their homeland, however, ostracized them as culturally estranged 'Germanized Turks' (Almancı). Through archival research and oral history interviews in both countries and languages, Michelle Lynn Kahn highlights migrants' personal stories and reveals how many felt foreign in two homelands. This title is also available as Open Access on Cambridge Core.